A form-based query interface for complex queries. (August 2015) - El-Mahgary, Sami; Soisalon-Soininen, Eljas
Abstract: It has been now well over thirty years since the advent of visual query systems (VQSs). Following a very active research period spanning from the late 1980s to the early 1990s, key research areas still remain, such as how to express complex queries in user-friendly fashion using a form-based query interface. A query is considered potentially complex from the user׳s point of view when it contains several entity sets and involves an aggregate operator and/or a many-to-many relationship set. This work examines such complex queries in the light of a form-based VQS, called OVI-2, and developed to handle the sophisticated query needs of users of the student records system at Aalto University, Otaniemi campus. Special emphasis is given to complex queries which involve existential quantification or its negation, such as finding students who have completed one given set of courses but who have not yet completed another given set of courses. User-friendliness was a key priority and was achieved mainly by using a two-phased approach for querying. The first stage focuses on retrieving all tuples and attributes that may be of interest, while in the second stage, users narrow down the set of tuples and select only the attributes that are actually needed. Although the presented VQS has been specifically developed for use with a student database, the key ideas are described in a generic way which should allow them to be used to query almost any database schema that has a many-to-many relationship set. Because OVI-2 was in active use for more than five years (over forty users had access to it), user feedback played a big role in this work. Many of the conclusions presented herein are based on observing users actually using OVI-2 to perform their timely query needs. Abstract : Highlights: A form-based visual query system, called OVI-2, capable of complex queries is presented. OVI-2 is contrasted with other VQS capable of expressing existential quantification. Users easily adapted to a form-based visual query system that provides enough expressive power.